Analisis Wacana Kritis Resistensi LGBT Menggunakan Akun Pseudonim Melalui Media Sosial Twitter - Ester Elisabeth Aspin N; Sunarto . (Interaksi Online, 2021)
The development of technology nowadays is impacting to all aspects in society life. One of the aspect that experiences the development is how the movement and resistance that are done by the minority groups to achieve their agenda. As technology advances, the resistance activity is not only done by conventional way but also using social media role as the medium. This research is aimed to see the reality about the resistance pattern that is done with pseudonym account through Twitter. This research uses qualitative method and critical discourse analysis as the research design by reffering to critical approach. The data collection method that is used in this research is divided into three steps which are Micro, Meso and Macro. In Micro, the data is collected by doing critical lingustic analysis to the text that is produced in the social media. In Meso, the data is gathered by doing indepth interview to the user of the pseudonym account and the consumer of the text. The last step is Macro which is done by analyzing the status quo in Indonesia that is related with the existance of LGBT in Indonesia. The teories which are used in this research are Resistance Theory and Queer Theory. The result of this research shows the journey of deciding to have the pseudonym account to do their resistance activity started when they experienced bad treatments from their environment when their identity was revealed. Therefore they use the pseudonym account as the response from people reaction toward their existance. By using that account, the agenda that they wish to achieve is to see more people know everything about LGBT better by consuming the text that is produced directly by the LGBT individual itself.